CEMPAKA: BUNGA RITUAL SAKRAL MASYARAKAT BALI - Ni Wayan Suartini (SURYA SENI, 2007)
Cempaka: Sacred Ritual Flower of Balinese People, recounts about ritual dialogue of human being to nature, spirits, and gods. This is a performance art  that locates and signiﬁ es the concept of space and time as a holistic unit toward movement arrangement upon artistic awareness and event creation.The Choreography of Cempaka is a revitalization of Puri Anyar palace as a  space governed by the concept of Tri Hita Karana (three causes harmony) and Tri Mandala (three integrated spaces) as a space that instigates choreographer’screative ideas to interact with the nature of Balinese cultural environment. This choreography integrates various aesthetic elements: dance, tembang song, music, decoration, and symbol of Balinese traditional house in the primary form ofpalace. Concept of the dance is derived from the function of space available in Puri Anyar palace.Puri Anyar palace has an historical and aesthetic values, which is traditional palace that observes the concept of Tri Mandala and in accordance with Asta Kosala-Kosali. The size dimension is sufﬁ cient and has a complete facility for a performance site of milieu choreography.  As a performance site, Puri Anyar palace is employed for performance without border between dancers and audience. The performance is presented for the entire social levels of local community, which is an integrated parts of the performance structure.Keywords: Performance arts, Cempaka ﬂ ower, Puri Anyar environment.